Determinan RAROC pada Perusahaan Manufaktur (LQ45) di Bursa Efek Indonesia (BEI) periode 2017 – 2023 - Ivan Jan Jaya Silaen; Adler Haymans Manurung; Jhonni Sinaga; Djuni Thamrin; AWN Fikri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the determinants of RAROC in manufacturing companies on the IDX for the 2017 - 2023 period. The data used in this research is secondary data. This data is quantitative data obtained from the Indonesian Stock Exchange (BEI) with shares included in the LQ45 Index in the form of annual financial reports for the period 2017 - 2023. The sample for this research was 33 companies obtained using purposive sampling technique. The data analysis technique used is multiple linear regression analysis and hypothesis testing using determinate coefficient tests, simultaneous F-tests and partial T-tests. The data analysis technique was carried out using the Eviews13 For Windows program. The research results show that Gross Profit Margin (GPM), Debt to Equity Ratio (DER) and Interest Coverage Ratio (ICR) together (simultaneously) have a significant effect on Risk-Adjusted Return on Capital (RAROC). Gross Profit Margin (GPM) partially has a negative and significant effect on Risk-Adjusted Return on Capital (RAROC), Debt to Equity Ratio (DER) partially has a positive and significant effect on Risk-Adjusted Return on Capital (RAROC) and Interest Coverage Ratio (ICR) partially has a negative and insignificant effect on Risk-Adjusted Return on Capital (RAROC).